A clash of characters: The effect of variation on a morphological hybrid index for an endangered California fairy shrimp Branchinecta sandiegonensis (Fugate, 1993) (Crustacea: Anostraca). Issue 3 (8th May 2018) - Patel, Ketan V; Simovich, Marie A; Graige, Nicholas S; Bohonak, Andrew J
Abstract: We validated the morphological hybrid index (MHI) described by Simovich et al. (2013) for detecting hybrids between the endangered San Diego fairy shrimp Branchinecta sandiegonensis (Fugate, 1993 ) and the versatile fairy shrimp B. lindahli (Packard, 1883 ) through morphological and genetic analysis of 662 individuals. This index uses species-specific character states for "spines" (dorsolateral projections) on thoracic segments 3–11 in adult females. In non-admixed (non-hybrid) populations, the character states for segment 8 correlate poorly with the remaining segments, and the overall morphological hybrid index score (MHI score). Only 22% of non-admixed B. sandiegonensis display the expected character state for segment 8 compared to nearly all B. lindahli . Eliminating this character in principal component analyses increases the proportion of variation explained by PC1 from 57.3% to 69.5%. The revised MHI, however, still shows slight variation in populations of B. sandiegonensis and B. lindahli that have no genetic evidence of admixture. Hybrid populations possess considerably more variation in MHI score, and this variation is heavily skewed towards B. lindahli phenotypes. We suggest using the revised MHI and genetic characters in future experimental field studies to improve an understanding of the processes that initiate and maintain hybridization in this system.